Level-set topology optimization for multimaterial and multifunctional mechanical metamaterials. Issue 1 (2nd January 2017) - Wang, Yu; Gao, Jie; Luo, Zhen; Brown, Terry; Zhang, Nong
ABSTRACT: Metamaterials are artificially engineered composites designed to have unusual properties. This article will develop a new level-set based topology optimization method for the computational design of multimaterial metamaterials with exotic thermomechanical properties. In order to generate metamaterials consisting of arrays of microstructures under periodicity, the numerical homogenization method is used to evaluate the effective properties of the microstructure, and a multiphase level-set model is used to evolve the boundaries of the multimaterial microstructure. The proposed method will produce material geometries with distinct interfaces and smoothed boundaries, which may facilitate the fabrication of the topologically optimized designs. Several numerical cases are used to demonstrate the effectiveness of the proposed method.